The estimation of atmospheric water vapour during monsoon season in northern region of Peninsular Malaysia - Nur Fadzlina Aini Mohmad Lehan, 1986-; Md. Nor Kamarudin; Fakulti Geoinformasi dan Harta Tanah (2012)
Thesis (Sarjana Sains (Navigasi Satelit)) - Universiti Teknologi Malaysia, 2012